Isometric versus isotonic exercise for greater trochanteric pain syndrome: a randomised controlled pilot study - Lorna Paul; Christopher Clifford; Neal L Millar; Grant Syme (BMJ Open Sport & Exercise Medicine)
Objectives Greater trochanteric pain syndrome (GTPS) is a common cause of lateral hip pain. Limited evidence exists for the effectiveness of exercise for GTPS. This study aimed to compare the effectiveness of isometric and isotonic exercise for individuals with GTPS.Methods This randomised controlled pilot trial recruited 30 participants with GTPS. Both programmes consisted of daily, progressive home exercise for 12 weeks with 8 individual physiotherapy sessions over the trial period. The primary outcome measure was the Victorian Institute of Sport Assessment-Gluteal (VISA-G) and secondary outcome measures included the Numeric Pain Rating Scale (0–10) and an 11-point Global Rating of Change Scale. Outcome measures were assessed at baseline, 4 and 12 weeks.Results Twenty-three participants completed the trial. After 12 weeks, mean VISA-G scores improved in both groups; 55–65 in the isometric group and 62–72 in the isotonic group. 55% of the isometric group and 58% of the isotonic group achieved a reduction in pain of at least 2 points (minimally clinically important difference (MCID)) on the Numeric Pain Rating Scale. 64% of the isometric group and 75% of the isotonic group had improved by at least 2 points (MCID) on the Global Rating of Change Scale.Conclusion Isometric and isotonic exercise programmes appear to be effective for individuals with GTPS and should be considered in the loading management of patients with this condition.